NRF2 Protects against Altered Pulmonary T Cell Differentiation in Neonates Following In Utero Ultrafine Particulate Matter Exposure - Carmen H. Lau; Drew Pendleton; Nicholas L. Drury; Jiayun Zhao; Yixin Li; Renyi Zhang; Gus A. Wright; Aline Rodrigues Hoffmann; Natalie M. Johnson (MDPI AG, 2022)
Early life exposure to particulate matter (PM) air pollution negatively impacts neonatal health. The underlying mechanisms following prenatal exposure, particularly to ultrafine particles (UFP, diameter ≤ 0.1 μm), are not fully understood; To evaluate the role of Nrf2 in response to in utero UFP exposure, we exposed time-mated Nrf2-deficient (Nrf2−/−) or wildtype (WT) mice to filtered air (FA) or 100 μg/m3 ultrafine PM daily throughout pregnancy. Offspring were evaluated for pulmonary immunophenotypes and pulmonary/systemic oxidative stress on postnatal day 5, a timepoint at which we previously demonstrated viral respiratory infection susceptibility; Nrf2−/− offspring exposed to FA had significantly lower average body weights compared to FA-exposed WT pups. Moreover, PM-exposed Nrf2−/− offspring weighed significantly less than PM-exposed WT pups. Notably, PM-exposed Nrf2−/− offspring showed a decreased pulmonary Th1/Th2 ratio, indicating a Th2 bias. Th17 cells were increased in FA-exposed Nrf2−/− neonates yet decreased in PM-exposed Nrf2−/− neonates. Analysis of oxidative stress-related genes in lung and oxidative stress biomarkers in liver tissues did not vary significantly across exposure groups or genotypes. Collectively, these findings indicate that the lack of Nrf2 causes growth inhibitory effects in general and in response to gestational UFP exposure. Prenatal UFP exposure skews CD4+ T lymphocyte differentiation toward Th2 in neonates lacking Nrf2, signifying its importance in maternal exposure and infant immune responses.